THE INFLUENCE OF SERVICE QUALITY ON TEACHER SATISFACTION IN THE JUNIOR HIGH SCHOOL COACHING SECTOR AT THE DEPARTMENT OF EDUCATION AND CULTURE OF HULU SUNGAI UTARA REGENCY - Khairil Anwar; Ni Made Musiyani Anjasmari; Nida Urahmah (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
The quality of public services is closely related to the capacity of service providers, responsiveness, timeliness, and the availability of facilities and infrastructure, thereby creating a dynamic interaction between service providers and service recipients. A service is considered to be of high quality when it is able to meet or exceed the expectations of its users. Conversely, if the service provided does not meet users’ expectations, it may be classified as low-quality service. This study employed a quantitative approach with a descriptive quantitative research design. Data were collected using three techniques, namely surveys, observations, and documentation. The data sources consisted of 75 respondents selected through accidental sampling. The collected data were then analyzed using IBM SPSS version 27 to determine the existence and strength of the influence of service quality on teacher satisfaction. Data analysis was conducted through a t-test, coefficient of determination (R²) test, and simple linear regression analysis. The results of the study indicate that service quality has a significant effect on the level of teacher satisfaction at the Junior High School Development Division of the Education and Culture Office of Hulu Sungai Utara Regency. This is evidenced by a calculated t-value of 18.074, which is greater than the t-table value (df = N–1) of 1.666, and a significance level of 0.000, which is lower than 0.10. Furthermore, the strong influence of service quality on teacher satisfaction is reflected in the magnitude of the relationship between the two variables, which reached 82%.